Menumbuhkan Minat Berwirausaha Bagi Santri Tahfidzul Qur'an Waadissalam Gowa Sulawesi Selatan - Andi Irfan; Andi Nuryadin; Amiruddin Amiruddin; Andi Irwan; Anzar Mulkin; Meldi leanas (Pusat Riset dan Inovasi Nasional, 2023)
Community Service Activities aim to identify and analyze effective strategies in fostering interest in entrepreneurship among Tahfidzul Qur'an students at the Waadissalam Islamic Boarding School in Gowa, South Sulawesi. Through training activities for students, how to foster a creative, innovative and independent entrepreneurial spirit. The results of the activity show that there has been an increase in terms of entrepreneurial desire, level of creativity, innovation and independence of the female students after the community service activities carried out by STIM-LPI Makasar lecturers. There is some increase in the desire or interest in entrepreneurship and creativity. It is hoped that the results of this Community Service activity can contribute to the development of education at the Waadissalam Islamic boarding school and encourage the development of interest in entrepreneurship among Tahfidzul Qur'an students. Apart from that, this Community Service Activity can also be a reference for other educational institutions in considering strategies to foster interest in entrepreneurship among their students.